E3 ubiquitin ligase ITCH improves LPS-induced chondrocyte injury by mediating JAG1 ubiquitination in osteoarthritis. (1st June 2022) - Qi, Liang; Wang, Min; He, Jinlong; Jia, Bin; Ren, Jing; Zheng, Shicheng
Abstract: ITCH is an E3 ubiquitin ligase associated with some inflammatory diseases, but its role in osteoarthritis (OA) remains to be explored. Here, we investigated the effects of ITCH in OA-induced chondrocyte damage and its potential mechanisms. Here, we found that ITCH was downregulated, while JAG1 was upregulated in OA tissues compared to normal cartilaginous tissues. And primary human chondrocytes were induced by LPS to simulate OA condition. Overexpressing ITCH or silencing JAG1 promoted proliferation, and restrained apoptosis, inflammation and extracellular matrix (ECM) degradation in LPS-stimulated chondrocytes. Mechanistically, ITCH bound to JAG1 protein through the WW-PPXY motif and degraded it via K48 ubiquitination. JAG1 overexpression reversed the protective effect of ITCH on LPS-induced chondrocyte damage. ITCH prevented LPS-caused Notch1 signaling activation by suppressing JAG1. Furthermore, GSI (a Notch specific inhibitor) abrogated the effects of ITCH knockdown on chondrocyte injury. Additionally, a mouse OA model was established by destabilization of the medial meniscus operation, and H&E and Safranin O-fast green staining was used to evaluate articular cartilage damage. And ITCH overexpression alleviated OA-induced articular cartilage damage in vivo . In conclusion, ITCH mitigated LPS-induced chondrocyte injury and OA-induced articular cartilage damage through attenuating Notch1 pathway activation by degrading JAG1 via ubiquitination, which provides a novel strategy for the treatment of OA. Highlights: ITCH suppresses LPS-induced primary human chondrocyte injury. ITCH degrades JAG1 protein via K48 ubiquitination. ITCH prevents LPS-caused Notch1 signaling activation by suppressing JAG1. ITCH overexpression alleviates articular cartilage damage in OA mice.